Análisis de la Sentencia N° 28-15-in/21 en decisiones judiciales del año 2023: implementación e igualdad de género - Guerrero Vera, Carla Daniela (2025)
The general objective of this investigation was to analyze how Judgment No. 28-15- IN/21 CC has been received in the judicial decisions issued by the competent courts of the city of Ibarra in the period January to December 2023, in order to analyze and identify if this sentence is actually being complied with. The research was carried out under the technique of documentary review, through the study of the files provided by the Council of the Judiciary of the care of Ibarra, from a mixed approach, covering qualitative and quantitative indicators, with a descriptive level of depth, in what is concerned with the implementation of the sentence with respect to gender equality. The methods used were the synthetic analytical, because it was related to the decomposition of the sentence and allowed the understanding of the parameters of it, the normative, which allowed the analysis of the legal and regulatory norms where the rights of children and adolescents are tacitly recognized. From the information obtained through the techniques and instruments used, it was possible to show that the application of the sentence is not completely executed in cases of possession of the NNA. Through the information analyzed from the files, it is concluded that, despite the limited application of the sentence in cases of tenure, there was an increase in the designation of tenure to the father, leaving aside gender stereotypes where it was stipulated that the woman was the most appropriate for the upbringing of the NNA, despite the fact that today there are still reasons under unconstitutional articles. Therefore, this study provided a detailed vision of the situation of tenure cases in Ibarra, identifying problems, challenges and contributing to gender equality in relation to the tenancy of children and adolescents.